2006
DOI: 10.1128/jb.188.8.2959-2973.2006
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of the ContiguoussigB,dtxR, andgalEGenes inCorynebacterium diphtheriae: Evidence for Multiple Transcripts and Regulation by Environmental Factors

Abstract: The iron-dependent transcriptional regulator DtxR from Corynebacterium diphtheriae is the prototype for a family of metal-dependent regulators found in diverse bacterial species. The structure of DtxR and its action as a repressor have been extensively characterized, but little is known about expression of dtxR. In the current study, we investigated transcription of dtxR as well as the sigB and galE genes located immediately upstream and downstream from dtxR, respectively. We identified two promoters that dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 66 publications
1
37
0
Order By: Relevance
“…C7(β)ΔdtxR::pK-AIM suppressed production of siderophore in the presence of FeCl 3 by approximately 6-fold but it produced approximately 10 times more siderophore under high-iron conditions than strains that expressed dtxR. This result is equivalent to that observed previously with C7(β)ΔdtxR (Oram et al, 2006). In contrast when pK-AIMdtxR was integrated into attB2 in C7(β)ΔdtxR (to form C7(β)ΔdtxR::pK-AIMdtxR) the ability to repress siderophore production by approximately 50-fold in the presence of FeCl 3 was restored.…”
Section: Complementation Of An Inactivated C Diphheriae Gene In Singsupporting
confidence: 79%
See 4 more Smart Citations
“…C7(β)ΔdtxR::pK-AIM suppressed production of siderophore in the presence of FeCl 3 by approximately 6-fold but it produced approximately 10 times more siderophore under high-iron conditions than strains that expressed dtxR. This result is equivalent to that observed previously with C7(β)ΔdtxR (Oram et al, 2006). In contrast when pK-AIMdtxR was integrated into attB2 in C7(β)ΔdtxR (to form C7(β)ΔdtxR::pK-AIMdtxR) the ability to repress siderophore production by approximately 50-fold in the presence of FeCl 3 was restored.…”
Section: Complementation Of An Inactivated C Diphheriae Gene In Singsupporting
confidence: 79%
“…In fact, while we had previously demonstrated that an intact copy of dtxR was able to reverse the phenotype of the C7(β)ΔdtxR strain when introduced in trans on a replicating plasmid (Oram et al, 2006), this work is the first to establish that a single copy of dtxR integrated into attB2 is capable of restoring DtxR functions to levels seen in a wild-type control. In addition, the inclusion of a transcriptional reporter gene to an integrating vector would permit characterization of the activity of a promoter in single copy from the C. diphtheriae chromosome.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations